A New Moldmade Bowl from Athens - Susan I. Rotroff (Ksiegarnia Akademicka Publishing, 2013)
A recently found Hellenistic moldmade bowl from the Athenian Agora displays a number of unusual features, but is most likely an Athenian product of the Workshop of Bion, a potter who produced moldmade bowls from the last quarter of the 3rd century until at least 175 BC. One of its stamps, a bull’s head, is closely paralleled on bowls made in Argos, and adds to previous evidence for a close relationship between the two producers.